Teaching Future Providers about Dementia: The Impact of Service Learning - Mahendra, Nidhi; Fremont, Karen; Dionne, Emily (Seminars in Speech and Language, 2013)
In this article, we describe an innovative approach for providing speech-language pathology graduate students with exposure to long-term care settings and clinical training in service delivery for persons with dementia. Our pedagogical approach emphasizes leading learners through distinct stages of creating awareness and a foundation of knowledge, teaching clinical skills, hands-on practice via service learning, and ongoing self-reflection. Outcome data presented in this article are derived from learner evaluations and written reflections as well as social validation data provided by dementia patients in a long-term care setting. Our findings reveal that a combination of high-impact practices, community-based service learning, and ongoing reflection can result in transformative learning and attitude shifts for speech-language pathology graduate students toward serving persons with dementia. This is a key finding given that a majority of our learners had little exposure to long-term care environments or had any prior interaction with persons with dementia.
Keywords: Dementia; long-term care; speech-language pathology; service learning